Avaliação dos principais parâmetros físicos e tecnológicos da borracha natural do clone RRIM 600 em diferentes frequências de sangria - Jorge, Ana Carolina Murback (Universidade Federal de São Carlos, 2022)
The latex of Hevea brasiliensis is the main feedstock raw material for obtaining natural rubber. Latex extraction is completely manual and is the activity with the highest percentage cost participation in the rubber tree production. There are different systems and intensities of tapping, but it is necessary to highlight those that present better productivity, lower cost and provide better latex quality and uniformity. The present work aimed to evaluate natural rubber parameters of the RRIM 600 clone under five different tapping frequencies. Two identical experiments were installed, differing only from the tapping agent. The study was held in the northwest region of the state of Sao Paulo, in the county of Jaci, under treatment of the following tapping frequencies: 1 /2S d/1 7d/7 10m/y; 1 /2S d/2 7d/7 10m/y; 1 /2S d/3 7d/7 10m/y; 1 /2S d/4 7d/7 10m/y and 1 /2S d/5 7d/7 10m/y. From four coagulated latex collections, in which the dry rubber content (DRC) and the plasticity retention index (PRI) were analyzed. The dry rubber content showed no statistical difference between the different treatments. Lower means were observed in the last collection in the treatment 1 /2S d/3 7d/7 10m/y of experiment 1 and in treatments 1 /2S d/1 7d/7 10m/y and 1 /2S d/4 7d/7 10m/y of experiment 2. All averages of plasticity retention index were below the minimum value specified by the national and international standard. In this parameter, lower means of PRI were noted in the most intense tapping frequencies. In experiment 1, the 1 /2S d/1 7d/7 10m/y treatment presented lower mean in collection 2. In experiment 2, in collection 3, treatments 1 /2S d/1 7d/7 10m/y, 1 /2S d/2 7d/7 10m/y and 1 /2S d/3 7d/7 10m/y 10m/y presented lower means. Also in experiment 2, in collection 4, treatments 1 /2S d/1 7d/7 10m/y, 1 /2S d/2 7d/7 10m/y and 1 /2S d/4 7d/7 10m/y presented lower means,
Evaluation of main physical and technological parameters of natural rubber from clone RRIM 600 under different tapping frequency
Keywords: Hevea brasiliensis; Latéx; Ensaios padrões; Qualidade; Standard test; Qualiity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA